Development of Video Tutorial for Pencak Silat Learning at State Junior High School 16 Pontianak - Muhammad Kautsar; Indri Astuti; Afandi Afandi (STKIP Singkawang, 2023)
The main objective of this research is to develop a video tutorial for Physical Education learning and to produce and disseminate a video tutorial for pencak silat learning. Then it is expected that the video tutorial can make it easier for students to learn pencak silat independently. This research uses the 4D model by Thiagarajan. The steps of the model are defined, designed, developed, and disseminated. The participants in this study were teachers and students of State Junior High School 16 Pontianak. Data collection techniques in this study refer to the interview list guidelines, namely questionnaires. The data collection tools are learning outcomes and questionnaire sheets. This pencak silat learning tutorial video was developed according to the needs and characteristics of students. Based on the data analysis of the experts' validation, the average of the design aspect is 3.87, the material aspect is 3.95, and the media aspect is 3.83. Including very valid criteria. The test of students' responses to the video tutorial for pencak silat learning obtained an average of 94.34%. Thus the video tutorial is very feasible to use in learning pencak silat class VII can be used on students by watching gadgets or other media. The purpose of this multimedia is so that students can understand and develop skill abilities in independent learning with video tutorials effectively.